2000
DOI: 10.1034/j.1399-3003.2000.15a38.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe tracheobronchial stenosis in a patient with Crohn′s disease

Abstract: Tracheobronchial involvement in Crohn's disease is rare, usually associated with symptoms of tracheobronchitis, and typically responds well to steroids. The authors report a case of a 29-yr old patient with Crohn's disease, who presented with dyspnoea, fever, and a productive cough. Computed tomography of the chest revealed extensive nodular tracheobronchial stenosis, that was accompanied by severe mucosal inflammation at bronchoscopy. High-dose oral steroids diminished the mucosal inflammation, but had limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…However, pulmonary lesions have been reported in patients with Crohn's disease, such as unexplained chronic bronchitis, bronchiolitis obliterans with organizing pneumonia, pleuropericarditis (1), recurrent pulmonary edema (3), granulomatous (4,5) and nongranulomatous interstitial pulmonary disease (6), granulomatous lung masses (7), bronchiectasis (8), and granulomatous bronchiolitis (9). Tracheal involvement in Crohn's disease is even more unusual and consists of mucosal inflammation (10)(11)(12). Drug therapy is another complicating factor, since sulfasalazine used in the treatment of Crohn's disease can also cause reactions in the lung (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…However, pulmonary lesions have been reported in patients with Crohn's disease, such as unexplained chronic bronchitis, bronchiolitis obliterans with organizing pneumonia, pleuropericarditis (1), recurrent pulmonary edema (3), granulomatous (4,5) and nongranulomatous interstitial pulmonary disease (6), granulomatous lung masses (7), bronchiectasis (8), and granulomatous bronchiolitis (9). Tracheal involvement in Crohn's disease is even more unusual and consists of mucosal inflammation (10)(11)(12). Drug therapy is another complicating factor, since sulfasalazine used in the treatment of Crohn's disease can also cause reactions in the lung (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic studies revealed polypoid or pseudotumoural structures and/or circumferential inflammation obstructing the airway lumen. These lesions were friable and haemorrhagic [16,43,[47][48][49]. Histological examination showed granulation tissue and mixed inflammation with domination of lymphocytes and plasma cells [43,[47][48][49].…”
Section: Airways Diseases -Larynx Trachea Bronchi Bronchiolimentioning
confidence: 99%
“…It may occur at any level from the larynx to the segmental bronchi [16,43,[47][48][49]. Clinical presentation in these cases included dyspnoea, fever, expectoration, stridor and/or wheeze [16,43,[47][48][49].…”
Section: Airways Diseases -Larynx Trachea Bronchi Bronchiolimentioning
confidence: 99%
See 1 more Smart Citation
“…UAD may present with hoarseness, stridor and severe respiratory distress or just with cough, phlegm and shortness of breath [43,44] . Physical examination may reveal wheezing during inspiration, expiration or both.…”
Section: Upper Airwaysmentioning
confidence: 99%